CIRCULATION MARINE DE LA LAGUNE DE NADOR (MAROC) PAR MODELISATION HYDRODYNAMIQUE - Karim, Hilmi; Ahmed, Makaoui; Mohammed, Idrissi; Benyounes, Abdellaoui; Zineb, El Ouehabi (European Scientific Journal, ESJ, 2015)
The marine circulation of Nador lagoon (Morocco) have been studied from April to July 2011 by hydrodynamic 3D model, under the new configuration of its new inlet which is operational from 2011. This study aims to understand the new mode of hydrodynamic functioning of this lagoon. The circulation in the lagoon is wind driven circulation, as the wind is contributing to mixing internally the lagoon waters. During the neap tides, the surface currents are very strong in the new inlet (> 1 m.s-1), less than 0.5 m.s-1 in the centre and 0.3 m.s-1 near the continental sides of the lagoon. The bottom currents are in the opposite direction from the surface currents and less than 0.2 m.s-1 .